Interfaces Conversacionais - Chatbot para a Casa da Música - Sara Filipa Gomes Oliveira (2017)
Conversational interfaces allow establishing a dialog among humans and machines that endeavor to replace humans as an informational intermediate on a dialog level. These interfaces can be voice assistants or chatbots. When using voice assistants the dialog is established via voice, while chatbots depend on textual methods. Xarevision S.A., a company related to informational systems for retail, created a project that comprises the development of a chatbot prototype to be used on Facebook Messenger. This inspired the prospect of cooperating with "Casa da Música", an institution related to cultural events. It's the "Casa da Música" cultural agenda that became the application area of this prototype. In order to identify how to obtain answers in a more quick and effective way while maintaining a user friendly experience, the aim of this dissertation is to characterize conversational interfaces in technological and functional terms. The advantages associated with its use and the evolution ever since its introduction will be identified as well as the top technologies used currently to develop this type of systems. This dissertation also has the goal of developing a prototype with the focus of searching and finding events in the agenda of "Casa da Música" and purchase tickets through a conversational interface, with the aim of obtaining experimental results and extract conclusions.